Metabolic Flexibility of Yarrowia lipolytica Growing on Glycerol - Egermeier, Michael; Russmayer, Hannes; Sauer, Michael; Marx, Hans (Frontiers in Microbiology, 2017)
The yeast Yarrowia lipolytica is a fascinating microorganism with an amazing metabolic flexibility. This yeast grows very well on a wide variety of carbon sources from alkanes over lipids, to sugars and glycerol. Yarrowia accumulates a wide array of industrially relevant metabolites. It is very tolerant to many environmental factors, above all the pH value. It grows perfectly well over a wide pH range, but it has been described, that the pH has a decisive influence on the metabolite pattern accumulated by this yeast. Here, we set out to characterize the metabolism of different Y. lipolytica strains, isolated from various environments, growing on glycerol at different pH values. The conditions applied for strain characterization are of utmost importance. Shake flask cultures lead to very different results, when compared to controlled conditions in bioreactors regarding pH and aeration. Only one of the tested strains was able to accumulate high amounts of citric acid in shake flask experiments, whereas a group of six strains turned out to accumulate citric acid efficiently under controlled conditions. The present study shows that strains isolated from dairy products predominantly accumulate sugar alcohols at any given pH, when grown on glycerol under nitrogen-limitation.